The endogenous HBZ interactome in ATL leukemic cells reveals an unprecedented complexity of host interacting partners involved in RNA splicing - Shallak, Mariam; Alberio, Tiziana; Fasano, Mauro; Monti, Maria; Iacobucci, Ilaria; Ladet, Julien; Mortreux, Franck; Accolla, Roberto S.; Forlani, Greta (Frontiers in Immunology, 2022)
Adult T-cell leukemia/lymphoma (ATL) is a T-cell lymphoproliferative neoplasm caused by the human T-cell leukemia virus type 1 (HTLV-1). Two viral proteins, Tax-1 and HBZ play important roles in HTLV-1 infectivity and in HTLV-1-associated pathologies by altering key pathways of cell homeostasis. However, the molecular mechanisms through which the two viral proteins, particularly HBZ, induce and/or sustain the oncogenic process are still largely elusive. Previous results suggested that HBZ interaction with nuclear factors may alter cell cycle and cell proliferation. To have a more complete picture of the HBZ interactions, we investigated in detail the endogenous HBZ interactome in leukemic cells by immunoprecipitating the HBZ-interacting complexes of ATL-2 leukemic cells, followed by tandem mass spectrometry analyses. RNA seq analysis was performed to decipher the differential gene expression and splicing modifications related to HTLV-1. Here we compared ATL-2 with MOLT-4, a non HTLV-1 derived leukemic T cell line and further compared with HBZ-induced modifications in an isogenic system composed by Jurkat T cells and stably HBZ transfected Jurkat derivatives. The endogenous HBZ interactome of ATL-2 cells identified 249 interactors covering three main clusters corresponding to protein families mainly involved in mRNA splicing, nonsense-mediated RNA decay (NMD) and JAK-STAT signaling pathway. Here we analyzed in detail the cluster involved in RNA splicing. RNAseq analysis showed that HBZ specifically altered the transcription of many genes, including crucial oncogenes, by affecting different splicing events. Consistently, the two RNA helicases, members of the RNA splicing family, DDX5 and its paralog DDX17, recently shown to be involved in alternative splicing of cellular genes after NF-κB activation by HTLV-1 Tax-1, interacted and partially co-localized with HBZ. For the first time, a complete picture of the endogenous HBZ interactome was elucidated. The wide interaction of HBZ with molecules involved in RNA splicing and the subsequent transcriptome alteration strongly suggests an unprecedented complex role of the viral oncogene in the establishment of the leukemic state.